Overweight Risk Factors Among Adolescents in Indonesia Based on Economic Level Disparities: A Nationwide Study - Nugroho, Purwo Setiyo; Umaroh, Ayu Khoirotul; Hattapradit, Faron (P3M Universitas 'Aisyiyah Surakarta, 2025)
Introduction: Overweight among adolescents in Indonesia is a growing public health issue, influenced by socioeconomic and lifestyle factors. Urbanization and economic disparities have contributed to increased consumption of calorie-dense foods and sedentary behaviors, particularly among adolescents from higher-income families. However, the role of economic status in shaping overweight risk remains underexplored. Objective: Examining socioeconomic disparities may influence the determinants of overweight in this population. Method: This cross-sectional study utilized secondary data from the Global School-based Student Health Survey (GSHS), encompassing 9,977 Indonesian students aged 11–18. The analysis included descriptive statistics, bivariate tests, and binary logistic regression to identify associations between behavioral, demographic, and socioeconomic variables and overweight status. The analysis was stratified by economic level, using hunger frequency as a proxy indicator. Result: Overall, 14.7% of adolescents were overweight. Sedentary behavior was significantly associated with overweight in both low and high economic groups. Among adolescents from higher economic backgrounds, junior high school students had a higher risk of being overweight compared to senior high school students. In contrast, no significant associations were found between overweight and other behavioral factors in the low economic group, except for sedentary habits. Conclusion: Sedentary behavior is a key risk factor for adolescent overweight across economic strata, while school level influences overweight risk in wealthier adolescents. These findings highlight the need for targeted interventions that address lifestyle behaviors and consider socioeconomic disparities to effectively combat adolescent overweight in Indonesia.